Influence of local leadership in poverty eradication among the Orang Asli communities in the state of Terengganu, Malaysia - Mohamad Hafis, Amat Simin; Mohamad Asmawi, Ibrahim; Ramle, Abdullah (Canadian Center of Science and Education, 2015)
Statistics show until now more than 30% of Orang Asli in Malaysia is still living in poverty. The government plans to eradicate the poverty facing many challenges. One of the challenges is related to the local synchronic factors, which include aspects of culture, belief, attitude, values and leadership. A survey was conducted on Kampung Orang Asli Sungai Pergam, Terengganu to identify the importance of the role of local leaders in ensuring the successful implementation of a development project that aims to poverty eradication among the local population. The village is chosen based on its performance in a number of development projects, and has successfully enhance socio-economic status of the population. Objective of the survey is to identify: (i) What are the characteristics that are capable of leadership impacts on local poverty alleviation project success. (ii) What role should be played by local leaders to make sure every development project undertaken to achieve objective. Survey data were collected by using interviews and observation techniques. Survey findings show personality traits of a leader is an important factor affecting the success of a leader of its own related to the implementation of development projects. In addition to the leadership structure also has a significance practiced in community development. From the point role of leadership, the element of awareness of the responsibility and commitment of the leaders in developing the village is important. Orang Asli leaders in the Kampung Sungai Pergam have initiative and commitment in ensuring their future progress of development for their village.